The Law of Nature, which Makes it Necessary to Develop the Fundamental Science of Cybernetics - Vitaliy Vyshinskiy (Кібернетика та комп'ютерні технології, 2023)
Understanding the environment ultimately boils down to the exploration of the laws of nature. Many years of experience have shown that not all of these laws are currently within the scope of scientists' attention. This law produces the development of fundamental sciences: physics, chemistry, botany, biology, including cybernetics, thereby defining its subject of research. This law and its connection with the scientific achievements of V.M. Hlushkova are considered in this work.